تقييم خدمات الإدارة الإلكترونية في قطاع التعليم العالي في سورية - العربيد عدنان; سلمان حيان; خضور أحمد (Latakia University Journal - Economic and Legal Sciences Series, 2013)
أصبح استخدام تكنولوجيا المعلومات والاتصالات في مؤسسات القطاع العام أمراً حتمياً في عصرنا الحالي, ويجسد مفهوم الإدارة الإلكترونية هذا الاستخدام, بما تحققه من مزايا وفوائد على صعيد التفاعل بين الدوائر العامة والمواطنين وقطاع الأعمال, وبين الدوائر والمؤسسات العامة فيما بينها, ورفع مستوى تقديم الخدمات العامة بالشكل الأمثل والأسرع والأقل كلفة, وفي سورية ينخفض بشدة مستوى تقديم الخدمات العامة الحكومية في ظل غياب الاستخدام الأمثل للتكنولوجيا في هذه المؤسسات, مع اختلاف درجة استخدام تكنولوجيا المعلومات والاتصالات من وزارة لأخرى, وفي قطاع التعليم العالي تقدم الوزارة عددا من الخدمات الإلكترونية من خلال بعض المواقع الإلكترونية, لكنها لم تصل إلى المستوى المطلوب لتحقيق الأداء الأمثل في تقديم الخدمات المتعلقة بالتعليم العالي, وفي هذا البحث سنحاول تقييم مستوى الخدمات الإلكترونية المقدمة في قطاع التعليم العالي في سورية. The use of information and communication technology in the public sector institutions is inevitable in the present age, the concept of e-administration embodies this use in an integrated manner, including demonstrable advantages and benefits at the level of interaction between public services and citizens, and the business sector, and between departments and public institutions among them, and raise the level of provision of public services optimally at the fastest and least expensive, in Syria level of providing public services has droped in the absence of optimal use of technology in these institutions, with a different degree of use of information technology and communications from Ministry to another, and in the higher education sector ministry provides a number of electronic services through some websites, but it did not reach the level required to achieve optimal performance in the provision of services related to higher education, and in this paper we will try to assess the level of electronic services provided in the higher education sectorin Syria .